Pelaksanaan Pendidikan Lintas Iman di Indonesia: Studi Kasus Pada Indonesian Conference on Religion and Peace (ICRP) - Salim, Arhanuddin (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
Religious education tends to overlook this aspect of respect for other religions. This article is the result of the research field by using a qualitative approach. The source of the data gathered from in-depth interviews, observes, and the documentation of the implementation of the Interfaith education on Indonesian Conference on Religion and Peace (ICRP). This article revealed that personal participant in inter-faith education implementation by ICRP underwent significant changes. On the aspect of their faith more confident with his religion, while still giving the fair space to good judgment and correct against other religions.